2022
DOI: 10.1155/2022/8304071
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Rehabilitation Training Based on Automatic Extraction Algorithm on Knee Anterior Cruciate Ligament Injury Caused by Exercise

Abstract: Objective. In order to explore the effect of rehabilitation training based on automatic extraction algorithm on knee anterior cruciate ligament reconstruction under arthroscopy.Methods. 81 patients with anterior cruciate ligament injury were randomly divided into observation group (42 cases) and control group (39 cases). The control group was given routine nursing, while the observation group was given rehabilitation training guidance based on automatic extraction algorithm. Lysholm score, HSS score, and range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the research of rehabilitation nursing plans, timely relief of pain and swelling is required after knee joint injury. (Zhu & Gao, 2022). For example, when a patient suffers from knee joint injury, rest and cold compression should be carried out immediately to prevent the knee joint from being extruded, coiled with gauze, or reduced in size, and to encourage and help the patient to properly carry out a recovery plan within a few weeks.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…In the research of rehabilitation nursing plans, timely relief of pain and swelling is required after knee joint injury. (Zhu & Gao, 2022). For example, when a patient suffers from knee joint injury, rest and cold compression should be carried out immediately to prevent the knee joint from being extruded, coiled with gauze, or reduced in size, and to encourage and help the patient to properly carry out a recovery plan within a few weeks.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%